2009
DOI: 10.1155/2010/596246
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Relapse to Significant Alcohol Drinking after Liver Transplantation

Abstract: The findings of the present study strongly support a required minimum of six months of abstinence before LT because duration of abstinence was found to be the strongest predictor of recidivism. Female sex, younger age at transplant and psychiatric comorbidities were also associated with relapse to harmful drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 24 publications
1
48
0
1
Order By: Relevance
“…Several larger studies evaluating rate of relapse and factors predicting relapse after liver transplantation are shown in Table 1, the relapse rate varies from 16% to 42% and harmful relapse rate varies from 10% to 18%. 11,[23][24][25][26][27][28][29][30][31][32][33] Various factors found to predictive of post-transplant alcohol relapse are shown in Table 2. Following variables have been shown to be associated with risk of post-transplant alcohol relapse: absence of structured management program pretransplant, length of pretransplant sobriety, alcohol or other substance dependence, prior alcohol rehabilitation, poor social support/lack of partner, poor psychosomatic prognosis or psychiatric comorbidity, female sex, patients' nonacceptance of having an alcohol problem before LT, continued alcohol use after liver disease diagnosis, low motivation for alcohol treatment, and presence of a first-degree relative with alcohol abuse in family.…”
Section: Predictors Of Relapsementioning
confidence: 99%
See 3 more Smart Citations
“…Several larger studies evaluating rate of relapse and factors predicting relapse after liver transplantation are shown in Table 1, the relapse rate varies from 16% to 42% and harmful relapse rate varies from 10% to 18%. 11,[23][24][25][26][27][28][29][30][31][32][33] Various factors found to predictive of post-transplant alcohol relapse are shown in Table 2. Following variables have been shown to be associated with risk of post-transplant alcohol relapse: absence of structured management program pretransplant, length of pretransplant sobriety, alcohol or other substance dependence, prior alcohol rehabilitation, poor social support/lack of partner, poor psychosomatic prognosis or psychiatric comorbidity, female sex, patients' nonacceptance of having an alcohol problem before LT, continued alcohol use after liver disease diagnosis, low motivation for alcohol treatment, and presence of a first-degree relative with alcohol abuse in family.…”
Section: Predictors Of Relapsementioning
confidence: 99%
“…Following variables have been shown to be associated with risk of post-transplant alcohol relapse: absence of structured management program pretransplant, length of pretransplant sobriety, alcohol or other substance dependence, prior alcohol rehabilitation, poor social support/lack of partner, poor psychosomatic prognosis or psychiatric comorbidity, female sex, patients' nonacceptance of having an alcohol problem before LT, continued alcohol use after liver disease diagnosis, low motivation for alcohol treatment, and presence of a first-degree relative with alcohol abuse in family. 11,[23][24][25][26][27][28][29][30][31][32][33] Pretransplant sobriety predicting absence of alcohol relapse after liver transplant is not a universal finding. 11,15,[23][24][25][26][27][28][29][30][31][32][33] Scoring systems also have been proposed to predict post-transplant alcohol relapse.…”
Section: Predictors Of Relapsementioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the studies supporting that the length of sobriety is a strong predictor of recidivism, there are others reporting that patients with a DSM-IV diagnosis of abuse had a lower relapse probability than those with alcohol dependence (DiMartini et al, 2006;Karim et al, 2010). DiMartini et al showed that variables such as alcohol dependence, short length of sobriety, family history of alcohol consumption and the use of other substances identified patients with a major risk of relapse (DiMartini et al, 2010).…”
Section: Abstinence Prior To Lt For Aldmentioning
confidence: 99%